HUBUNGAN SELF CARE DENGAN KUALITAS HIDUP PASIEN DIABETES MELITUS (DM) - Fitri Handayani; Domianus Namuwali; Maria Fatima Saga Wea (Journal of Innovation Research and Knowledge, 2024)
Background: Increasing public awareness about the risk factors and prevention of diabetes is key to controlling the prevalence of this disease. Through appropriate interventions, the health burden of diabetes mellitus can be reduced, so that the quality of life of patients can be improved. Methods: The type of research used was quantitative with a cross sectional study design. Respondents in this study were 76 respondents, carried out in the Sikumana Health Center Working Area of Kupang City. Results: It is known that out of 27 people with low self-care 15 people (20%) of them have a good quality of life, 12 people (16%) of them have a fair quality of life. Whereas from 49 people with moderate self-care 46 people (61%) of them have a good quality of life and a fair quality of life as many as 3 people (3%). The results of Chi-Square Tests show that there is a relationship between self care and quality of life in patients with Diabetes Melitus. Conclusion: there is a relationship between self care and quality of life in patients with Diabetes Mellitus.